2021
DOI: 10.1007/s10447-021-09436-y
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Bayesian Racism Scale: Measuring Endorsement of Racial Stereotypes

Abstract: Bayesian racism is the belief that it is rational to discriminate against people based on existing racial stereotypes. The presence of Bayesian racism is strongly associated with negative feelings about minoritized groups and the desire to maintain racially inequitable social hierarchies. A confirmatory factor analysis on the Bayesian Racism Scale (BRS) yielded a unidimensional measure for assessing prejudicial attitudes that endorse stereotypes based on racial and ethnic groups. Findings from the study have i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…Specifically, priming of therapists with stereotypes of black people was subsequently associated with their assessing a fictional client as being more hostile (Abreu, 1999). The use of an explicit measure assessing a construct called Bayesian racism has recently been proposed by scholars for use in the counseling field (Litam et al, 2022;Litam & Balkin, 2021). The proposed Bayesian Racism Scale is a measure of one's belief in the rationality of discriminating based on racial stereotypes (Uhlmann et al, 2010).…”
Section: Stereotyping and Biases In Counselingmentioning
confidence: 99%
See 1 more Smart Citation
“…Specifically, priming of therapists with stereotypes of black people was subsequently associated with their assessing a fictional client as being more hostile (Abreu, 1999). The use of an explicit measure assessing a construct called Bayesian racism has recently been proposed by scholars for use in the counseling field (Litam et al, 2022;Litam & Balkin, 2021). The proposed Bayesian Racism Scale is a measure of one's belief in the rationality of discriminating based on racial stereotypes (Uhlmann et al, 2010).…”
Section: Stereotyping and Biases In Counselingmentioning
confidence: 99%
“…The proposed Bayesian Racism Scale is a measure of one's belief in the rationality of discriminating based on racial stereotypes (Uhlmann et al, 2010). Researchers have suggested that counselors may use their results on this scale to reflect on their own possible tendencies towards stereotyping (Litam & Balkin, 2021).…”
Section: Stereotyping and Biases In Counselingmentioning
confidence: 99%